2020
DOI: 10.1021/acs.analchem.0c02745
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Exosome Analysis Methods with an Emphasis on Electrochemistry

Abstract: Advances in Exosome Analysis Methods with an Emphasis on ElectrochemistryExosomes, small extracellular vesicles, are released by various cell types. They are found in bodily fluids, including blood, urine, serum, and saliva, and play essential roles in intercellular communication. Exosomes contain various biomarkers, such as nucleic acids and proteins, that reflect the status of their parent cells. Since they influence tumorigenesis and metastasis in cancer patients, exosomes are excellent noninvasive potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…[ 86 ] However, the rare existence of cancer‐derived exosomes places strained access for both effective extraction and sensitive identification. [ 87 ] Fu et al reported an electrochemical assay using magnetic NPs to selectively capture two markers (α‐synuclein and synthetic‐1) from neuronal exosomes (Figure 5B). [ 88 ] The cohort study of α‐synuclein level across 40 clinical samples was conducted to distinguish Parkinson's disease patients ( n = 20 per group) from healthy controls toward precise diagnostics.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…[ 86 ] However, the rare existence of cancer‐derived exosomes places strained access for both effective extraction and sensitive identification. [ 87 ] Fu et al reported an electrochemical assay using magnetic NPs to selectively capture two markers (α‐synuclein and synthetic‐1) from neuronal exosomes (Figure 5B). [ 88 ] The cohort study of α‐synuclein level across 40 clinical samples was conducted to distinguish Parkinson's disease patients ( n = 20 per group) from healthy controls toward precise diagnostics.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Electrochemical biosensor has been recognized as an excellent platform for biological sample analysis due to its advantages of high sensitivity, low cost, rapid response and low sample volume. 171,172 Several classic electrochemical techniques are frequently utilized in bioassays, including amperometry, voltammetry, impedimetry and field effect transistor. Nanomaterials mainly play two vital roles in these techniques: as the electrode substrate to improve the electron transfer and as the functional nanotags for signal amplification.…”
Section: Nanomaterials-based Electrochemical Biosensors For Exosome Detection Electrochemical Biosensorsmentioning
confidence: 99%
“…Apart from traditional methods including nanoparticle tracking analysis (NTA), western blot, flow cytometry, and enzyme-linked immunosorbent assay (ELISA) [ 11 ], various biosensing platforms have been developed for exosomes analysis by targeting their surface proteins using the corresponding antibodies or aptamers [ 12 17 ]. Among them, surface plasma resonance (SPR) biosensor is receiving extensive attention because it is a rapid, real-time, and label-free diagnostic device [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%